Introduction of the Internet of Things as a Debriefing for Students with Cross Interests in Information Technology and Computers - Imam Riadi; Sunardi; Denis Prayogi; Restu Prima Yudha; Muchrisal (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Hangtuah Tarakan High School is one of the secondary schools in Tarakan City that has ICT cross-interest subjects. This subject is followed by students of class XI and XII from the Department of Mathematics and Natural Sciences (MIA) and Social Sciences (IIS). The focus of this study is embedded systems using sensors and microcontrollers. For learning to be optimized and related to current technological developments in the Industry 4.0 era, an introduction to the Internet of Things (IoT) is held to open students' insight and knowledge. The seminar using the presentation method (lecture) which was attended by 35 participants was held in the school's computer laboratory. Based on the initial survey conducted regarding the material to be presented, the participant’s knowledge about the material was categorized as not understanding with a score of 2.42 on the Linkert 5 scale. The school in collaboration with the Faculty of Industrial Technology through the Master Program of Informatics held a seminar on the introduction of IoT on August 22, 2022. The 195-minute event from 11.45–15.00 received an enthusiastic welcome from the participants so that their understanding of the material increased. Based on the post-test survey, the level of understanding of the participants increased to a score of 3.64 on a score scale of 5 and entered the criteria for very understanding